Knowledge, attitude and practice on road traffic safety among the motorbike riders of Lalitpur metropolitan, Nepal - Phuyal, Sujeeta; Ghimire, Sushmita; Adhikari, Anita; Khadka, Debendra; Pahari, Sandip (International Journal Of Community Medicine And Public Health, 2024)
Background: Motorbike riders are among the most vulnerable road users, and road safety plays a primary role in eliminating road traffic accidents (RTAs). The objective of the study was to determine the level of knowledge, attitude and practice of road safety among motorbike riders and to identify the factors associated with their knowledge, attitude and practices. Methods: This was a cross-sectional study was conducted among 151 motorbike riders utilizing face-to-face interview. Systematic sampling technique was applied to 1516 households of the selected ward. Socio-demographics and KAP were obtained using structured questionnaire. Bivariate and multivariate analysis was done to find out the association between independent and dependent variables. Results: Overall, only (62.9%) respondents had adequate knowledge of road safety; (73%) of riders had a favorable attitude toward road safety; while only (44.37%) followed good road safety practices. The practice of drunken-drive was reported by total of 33.2% of respondents. Results showed that over speeding practices were (5 times) higher in males, mobile use was seen more (7.4 times) among age group 18-24. The more the years of riding experience the more the speedy driving, i.e. (1.08 times) higher among those having more than 2 years of riding experience. Conclusions: To address RTA through, we conclude that traffic police and other stakeholders should implement robust legislation concerning road safety. This should include periodic training and examinations for vehicle users to ensure their understanding and compliance with road safety measures.